Antitrust settlements how a simple agreement can drive the economy - Massarotto, Giovanna (International competition law series., 2019)
Competition enforcement authorities use settlements as a tool to ensure compliance with antitrust law. Companies can make commitments to remedy breaches, ensuring that they avoid litigation and potential fines and reputational damage. The author of this innovative book shows that, rather than fines or arguing principles of competition law in litigation, antitrust settlements (namely U.S. consent decrees and EU commitment decisions) hold the key to globally effective enforcement, particularly in the digital and blockchain era. Antitrust law does not necessarily need to be abolished, but rather should be fully exploited as an economic regulation led by antitrust settlements.